If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15x^2-18x-36=0
a = 15; b = -18; c = -36;
Δ = b2-4ac
Δ = -182-4·15·(-36)
Δ = 2484
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{2484}=\sqrt{36*69}=\sqrt{36}*\sqrt{69}=6\sqrt{69}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-18)-6\sqrt{69}}{2*15}=\frac{18-6\sqrt{69}}{30} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-18)+6\sqrt{69}}{2*15}=\frac{18+6\sqrt{69}}{30} $
| -3v+3=-7+2v | | 6x+4x=10x | | 25x+3=10x+27 | | X+x=8x-x=6x+x=13x+x=8 | | 3s=1+2s | | 4u-9=3 | | 3+6x=8-3x | | F(2)=2x+2 | | -4x+2=8x-46 | | 5x-x–34=2 | | -156=4(-7+8x) | | a+89=3 | | 3(x+29)=75 | | w(3w+23w)=8 | | 14^2x=3^-x+4 | | 12m+9=2m+29 | | 4w+3=5(2w-3) | | 13x-7=58 | | H(x)=X+5/3-X | | w6=7 | | 2(2x+3)=4(x+6) | | 7x-4(x+3)=6x-3(x+4) | | 9r=-81 | | 4(2x-3)=8x-1 | | 50+1.5m=65+1.05m | | n^2+5n=0.2677 | | -8(8x+6)=6x+22 | | 55/100=x/60 | | -3(2c-5)=15 | | 2/3x=-60 | | 1/x=20/14 | | -7/3m-2=-2m+m-2/3 |